Generic models for business applications. Towards a framework for identification and assessment - Schanda, Angelika (2015)
This thesis proposes a framework for identifying and assessing generic system dynamics models in business and suggests a list of candidate models. Results are meant to support isee systems, inc. in its aim to make system dynamics more accessible to managers and to further develop knowledge in the field. The main contributions of this study are a) synthesizing the current discourse not only theoretically by a literature review, but also empirically by interviews with experts b) offering concrete steps in form of an operative framework and c) relating problems with the concept of generic models to critical problems in the field. The main limitation of this study is that practical testing of the framework was not possible. Results of the empirical study suggest that the operative framework needs to be further developed because there is substantial disagreement on underlying theories in the conceptual framework. Therefore, the operative steps can only be seen as tentative and as a starting point for further research.